Modern methods of organic synthesis - Carruthers, W (Cambridge University Press, 2004)
Rev. ed. of: Some modern methods of organic synthesis. 3rd ed. 1986; Includes bibliographical references and index; Formation of carbon-carbon single bonds -- Formation of carbon-carbon double bonds -- Pericyclic reactions -- Radical and carbene chemistry -- Functionalization of alkenes -- Oxidation -- Reduction